Thymic Carcinoma Presenting as Disseminated Intravascular Coagulation. (11th November 2014) - Siricilla, Mamatha; Memon, Jawairia; Avery, Robert
Abstract : Thymomas and thymic carcinomas are rare tumors, which originate from the epithelial cells of the thymus. We present a case of thymic carcinoma, which presented with DIC as an initial manifestation. DIC improved with corticosteroid treatment and thymic carcinoma was amendable to chemoradiation.